Rituals and Sisterhoods : Single Women's Households in Mexico, 1560-1750 - Megged, Amos (University Press of Colorado, 2019)
"An approach to lingering views on single, plebeian women in Latin American historiography and specifically Mexico. Major revelations that single women in lower echelons of society in early to mid-colonial Mexico were able to transcend class and race barriers in spite of poverty and unfavorable social circumstances"--Provided by publisher